From film tourism to media pilgrimage: visiting the ‘real Mama-Coco’ in Indigenous Mexico - Alvarado Sizzo, Ilia; Sánchez Aguirre, Driselda P.; Aldaz Galicia, Norma Yadira (Economía Sociedad y Territorio, 2024)
This research analyzes the phenomenon of tourist travel to some destinations in relation to the animated film Coco, based on the Day of the Dead tradition celebrated in Mexico, and the motivations of tourists to travel; Thus, from a qualitative approach, it is shown how visitors of “Mama Coco” in Michoacan incur in behavioral patterns explained by the concept of media pilgrimage, but unlike similar trips, commonly linked to sites, in this case the center is found in a person whom they associate with feelings of nostalgia and family ties.